Maintaining momentum to 2015? : an impact evaluation of interventions to improve maternal and child health and nutrition outcomes in Bangladesh - White, Howard, 1960- (World Bank operations evaluation study., 2005)
This report addresses the issue of what publicly-supported programs and external assistance from the Bank and other agencies can do to accelerate attainment of targets such as reducing infant mortality by two-thirds. The evidence presented here relates to Bangladesh, a country which has made spectacular progress but needs to maintain momentum in order to achieve its own poverty reduction goals. The report addresses the following issues:(1) What has happened to child health and nutrition outcomes and fertility in Bangladesh since 1990? Are the poor sharing in the progress which is being made?).